2012
DOI: 10.1021/np200989t
|View full text |Cite
|
Sign up to set email alerts
|

Kaurenoic Acid from Sphagneticola trilobata Inhibits Inflammatory Pain: Effect on Cytokine Production and Activation of the NO–Cyclic GMP–Protein Kinase G–ATP-Sensitive Potassium Channel Signaling Pathway

Abstract: Kaurenoic acid [ent-kaur-16-en-19-oic acid (1)] is a diterpene present in several plants including Sphagneticola trilobata. The only documented evidence for its antinociceptive effect is that it inhibits the writhing response induced by acetic acid in mice. Therefore, the analgesic effect of 1 in different models of pain and its mechanisms in mice were investigated further. Intraperitoneal and oral treatment with 1 dose-dependently inhibited inflammatory nociception induced by acetic acid. Oral treatment with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
72
2
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(81 citation statements)
references
References 35 publications
6
72
2
1
Order By: Relevance
“…2,9,10,35 Despite the importance of sesquiterpenes on the chemical and biological characterization of Copaifera oleoresins, [1][2][3][17][18][19] recent reports have established that several non-volatile diterpenes, such as (-)-copalic acid, ent-kaurenoic acid and (-)-polyalthic acid, are also responsible for important biological properties displayed by these balsams. 3,11,12,14,15,22 Even though and as stated before, there are only two analytical methods to characterize these diterpene acids in Copaifera oleoresins. 9,21 Concerning to diterpenes, the literature 11,17,36 reported that (-)-copalic acid (4) can be found in all oleoresins of Copaifera species and that it has been proposed as the chemical marker of the genus.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…2,9,10,35 Despite the importance of sesquiterpenes on the chemical and biological characterization of Copaifera oleoresins, [1][2][3][17][18][19] recent reports have established that several non-volatile diterpenes, such as (-)-copalic acid, ent-kaurenoic acid and (-)-polyalthic acid, are also responsible for important biological properties displayed by these balsams. 3,11,12,14,15,22 Even though and as stated before, there are only two analytical methods to characterize these diterpene acids in Copaifera oleoresins. 9,21 Concerning to diterpenes, the literature 11,17,36 reported that (-)-copalic acid (4) can be found in all oleoresins of Copaifera species and that it has been proposed as the chemical marker of the genus.…”
Section: Resultsmentioning
confidence: 99%
“…Acid diterpenes stands out for a wide range of the biological properties reported for these oleoresins, such as: antimicrobial, antitumoral, antinociceptive and anti-inflammatory, among others. 3,4,6,[11][12][13][14][15] Despite this fact, most of the studies reporting the chemical identification and quantification of the diterpenes of Copaifera oleoresins have been performed by using gas chromatographic hyphenated 9 only comprises the analysis of one standard ((-)-copalic acid) in commercial samples of oleoresins and the study published by Mangabeira et al…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Among the biological effects of this diterpene, studies have shown analgesic activity (Mizokami et al, 2012), antiinflammatory effects in asthma models (Cho et al, 2010), antitumoral, antimicrobial and antiprotozoal actions (Costa-Lotufo et al, 2002;Wilkens et al, 2002;Izumi et al, 2012;Santos et al, 2013).…”
Section: Introductionmentioning
confidence: 99%